Decision Analysis Expert Use - Morris, Peter A. (Management Science, 1974)
This paper is the first in a series of articles introducing a new conceptual and methodological framework for the use of experts in decision situations. Presented is the first theory of expert resolution wholly consistent with the Bayesian or subjectivist view of probability. The approach taken rests philosophically on the foundations of decision analysis. The results form practical tools for solving expert resolution problems. The present paper develops a structure in which the expert resolution problem may be logically formulated and conceptually solved. A framework is developed which enables a decision maker to encode his state of information concerning an expert. Application of the tools of Bayesian inference provides a mechanism by which a decision maker can incorporate an expert's opinion into his own. The more complicated case in which a decision maker is confronted with the diverse judgments of more than one expert is also addressed in detail. Additionally, the problem of determining the economic worth of one or a panel of experts is presented.